Hydrophobic interactions between polymeric carrier and palmitic acid-conjugated siRNA improve PEGylated polyplex stability and enhance in vivo pharmacokinetics and tumor gene silencing. (August 2016) - Sarett, Samantha M.; Werfel, Thomas A.; Chandra, Irene; Jackson, Meredith A.; Kavanaugh, Taylor E.; Hattaway, Madison E.; Giorgio, Todd D.; Duvall, Craig L.
Abstract: Formation of stable, long-circulating siRNA polyplexes is a significant challenge in translation of intravenously-delivered, polymeric RNAi cancer therapies. Here, we report that siRNA hydrophobization through conjugation to palmitic acid (siPA) improves stability, in vivo pharmacokinetics, and tumor gene silencing of PEGylated nanopolyplexes (siPA-NPs) with balanced cationic and hydrophobic content in the core relative to the analogous polyplexes formed with unmodified siRNA, si-NPs. Hydrophobized siPA loaded into the NPs at a lower charge ratio (N + :P − ) relative to unmodified siRNA, and siPA-NPs had superior resistance to siRNA cargo unpackaging in comparison to si-NPs upon exposure to the competing polyanion heparin and serum. In vitro, siPA-NPs increased uptake in MDA-MB-231 breast cancer cells (100% positive cells vs. 60% positive cells) but exhibited equivalent silencing of the model gene luciferase relative to si-NPs. In vivo in a murine model, the circulation half-life of intravenously-injected siPA-NPs was double that of si-NPs, resulting in a >2-fold increase in siRNA biodistribution to orthotopic MDA-MB-231 mammary tumors. The increased circulation half-life of siPA-NPs was dependent upon the hydrophobic interactions of the siRNA and the NP core component and not just siRNA hydrophobization, as siPA did not contribute to improved circulation time relative to unmodified siRNA when delivered using polyplexes with a fully cationic core. Intravenous delivery of siPA-NPs also achieved significant silencing of the model gene luciferase in vivo (∼40% at 24 h after one treatment and ∼60% at 48 h after two treatments) in the murine MDA-MB-231 tumor model, while si-NPs only produced a significant silencing effect after two treatments. These data suggest that stabilization of PEGylated siRNA polyplexes through a combination of hydrophobic and electrostatic interactions between siRNA cargo and the polymeric carrier improves in vivo pharmacokinetics and tumor gene silencing relative to conventional formulations that are stabilized solely by electrostatic interactions.